2012
DOI: 10.1097/rti.0b013e31825d515b
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Strategic Management of Subsolid Pulmonary Nodules

Abstract: A new classification of lung adenocarcinoma has been proposed recently-the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification. Abundant information from recent lung cancer computed tomography (CT) screening programs has increased our understanding of the strong, although imperfect, correlation between histologic findings of lung adenocarcinoma and subsolid pulmonary nodules on CT, including both "pure" ground-glass nodules (GGNs) and "pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…This classification would influence the next revision of the turnour, node, metastasis (TNM) staging classification. Studies have shown a close correlation between histological and CT findings [11,49,50]. On CT, AAH tends to present as a small pure GGO lesion that typically measures ,5 mm in diameter but can be as large as 1-2 cm.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This classification would influence the next revision of the turnour, node, metastasis (TNM) staging classification. Studies have shown a close correlation between histological and CT findings [11,49,50]. On CT, AAH tends to present as a small pure GGO lesion that typically measures ,5 mm in diameter but can be as large as 1-2 cm.…”
Section: Discussionmentioning
confidence: 91%
“…MIA has an excellent prognosis with almost 100% disease-specific survival, similar to AIS. Invasive adenocarcinoma usually manifests as a solid nodule or part-solid GGO lesion, only rarely appearing as having pure GGO [49].…”
Section: Discussionmentioning
confidence: 99%
“…To date, imaging features have not been sufficiently described for MIAs; however, nonmucinous MIAs have been shown to appear as part-solid GGNs with a small solid component ≤5 mm (Fig. 3) or as pure GGNs (1,11). Mucinous MIAs are much less frequent and may present as predominantly solid nodules (1).…”
Section: Ct-pathologic Correlations Of Subsolid Nodulesmentioning
confidence: 99%
“…3) or as pure GGNs (1,11). Mucinous MIAs are much less frequent and may present as predominantly solid nodules (1).…”
Section: Ct-pathologic Correlations Of Subsolid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation